bub1 as a potential oncogene and a prognostic biomarker for neuroblastoma - Song, Jingjing; Ni, Chao; Dong, Xubin; Sheng, Chenang; Qu, Yue; Zhu, Libin (Frontiers in Oncology, 2022)
Background: Neuroblastoma is the most common malignant extracranial tumor for children. Molecular mechanisms underpinning the pathogenesis of this disease are yet to be fully clarified. This study aimed to identify a novel oncogene that could be used as a biomarker informing the prognosis of neuroblastoma, and to predict its biological functions, using bioinformatics and molecular biology tools. Methods: Three data sets from the TARGET, GSE62564, and GSE85047 databases were used for analysis. Survivals of patients with high or low expression of bub1 were compared, using the Kaplan-Meier curve and log-rank test. Immune infiltration was evaluated using ESTIMATE and MCP-counter algorithms. Synthetic small interfering RNAs (siRNAs) were employed to silence bub1 expression in neuroblastoma cell lines SH-SY5Y and SK-N-SH, in order to characterize its biological functions. Gene enrichment analyses of bub1 were carried out, using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses. Results: Expression of bub1 was found to significantly affect overall survival and event-free survival of patients with neuroblastoma, positively correlate with the expressions of tpx2 and the ASPM gene, and negatively correlate with host immune infiltration. Expression of bub1 was elevated in patients with neuroblastoma. Silencing bub1 expression using siRNAs in SH-SY5Y and SK-N-SH resulted in decreased cell growth (p < 0.05), reduced migration (p < 0.05), and increased apoptosis (p < 0.05). Function analysis of bub1 revealed cancer-promoting effects, probably via regulating several important downstream molecules, including that related to the apoptosis process and epithelial-mesenchymal transition. Conclusion: We identified a potential tumor-promoting gene bub1 for neuroblastoma that could also serve as a prognostic biomarker.